Rancangan Sistem Informasi Penjualan Pakaian Muslimah Berbasis Android di Toko Andiza - Muhammad Rizky Alrazyd; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2021)
The current state of stores offering products in the traditional way is that consumers come to the seller to see what they have to offer. This problem is a big stumbling block to sales. With increasing quality, reputation increases and is good in the eyes of customers who sell clothes, so it is necessary to consider the quality of the product to be produced. The problems that occur in shops are still using the traditional way of serving consumers, so there is no solution designed to help sellers sell their products throughout Indonesia. The proposed system method used in this study includes the creation of Android-based software using the Kotlin and Java programming languages, design, code generation, and black-box testing methods. The results of several system methods used are very good from design to testing, but there are several features that must be developed by the seller to make it easier for buyers to get the product they want.